2009
DOI: 10.1386/eta.5.2and3.169/1
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from the landscape: an integrated approach

Abstract: This article presents a multidisciplinary pedagogy that integrates art education and ecological studies toward the goal of fostering affection for the landscape. This approach to designing art curriculum was based on ecological and outdoor education Expeditionary Principles. Learning objectives that are common to art education and Expeditionary Principles are discussed. A model for teaching environmental education through art was incorporated in the design of a graduate professional development course for tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Special education faculty must realize that they need to alter their own teaching styles, from giving information to encouraging peer collaboration, risk taking, problem solving, and decision making. Faculty must emphasize the importance of self-reflection, and through the reflective practice, students’ confidence and reliance on their own instincts will increase (Miraglia & Smilan, 2009). The faculty is still responsible for all students’ learning and for accomplishing the course goals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Special education faculty must realize that they need to alter their own teaching styles, from giving information to encouraging peer collaboration, risk taking, problem solving, and decision making. Faculty must emphasize the importance of self-reflection, and through the reflective practice, students’ confidence and reliance on their own instincts will increase (Miraglia & Smilan, 2009). The faculty is still responsible for all students’ learning and for accomplishing the course goals.…”
Section: Discussionmentioning
confidence: 99%
“…Contu and Willmott (2003) studied the ways in which situated learning strengthens students’ abilities to fine-tune their skills as they practice within the organizational context that they planned to enter after their education. Researchers found that when students’ learning was embedded in the context itself, it was more meaningful, and was valued more highly in the workplace and the community (Miraglia & Smilan, 2009). The special education graduate students learned to apply specific learning through authentic hands-on activities as they collaborated with peers and reflected on their own teaching practice.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…We become aware of how we are embedded in an ecosystem; in a landscape with particular flora and fauna; in a particular social system and culture." (Miraglia & Smilan, 2009).…”
Section: Lessons Learned From the Landscapementioning
confidence: 99%